Pathogenesis of COVID-19 and multi-system inflammatory syndrome in children - Shankaralingappa, Arundhathi; Thirunavukkarasu, Arun Babu (International Journal of Contemporary Pediatrics, 2021)
World health organization declared COVID-19 caused by SARS CoV-2 virus as a pandemic in early 2020. The target cells facilitating viral entry are ACE-2 receptor bearing cells like bronchial epithelial cells and pneumocytes. Children pose a less risk compared to adults in acquiring this disease and mortality in them is low due to protective pathogenesis. Children with COVID-19 are also at risk of developing unique immunological phenomena, known as multi-system inflammatory syndrome in children. MIS-C is considered to be hyperimmune state resulting from cytokine storm and circulating immune complexes. This mini-review reflects the most recent understanding of the pathogenesis in children with special emphasis on MIS-C.